Information Services Using the Small Group Discussion Learning Method to Improve Students' Interpersonal Communication Skills - Kurniawan, Rizki; Firman, Firman; Netrawati, Netrawati (Widyagogik, 2023)
This literature study research aims to determine the effectiveness of the small group discussion method to improve students' interpersonal communication skills. The 21st century learning skills in students' interpersonal communication skills are still relatively low because the learning strategies used by teachers are still not precise and effective. The learning process still uses teacher center so that students only listen and take notes. As a result, students' interpersonal communication skills are still relatively low, so the small group discussion method is applied during learning. This research is a literature study research. The data collection technique used is Editing by combining data from the results of article analysis. The data analysis used is deductive data analysis, that is, general facts are made to be more specific. The source of this research is to use secondary sources and primary sources. The results of the literature review in this study showed that the use of the small group discussion method, namely the interaction of 4-5 members of a group of students to solve a problem, thus showing an increase in communication skills such as grammar, conveying ideas, clarity of pronunciation and clarity of delivery of material and increased communication skills interpersonal students such as exchanging opinions, arguments, respecting opinions and making conclusions based on the results of the post test in previous studies compared to the results of the pre-test of students before being given action.